Are there bubbles in shipping freight during COVID-19? - Khan, Khalid; Khurshid, Adnan; Koseoglu, Sinem Derindere (Elsevier Sci Ltd, 2023)
This study examines the potential bubbles' shipping freight rates during the pandemic through the Generalized Supremum Augmented Dickey-Fuller test. The results explore multiple bubbles in the freight rates during corona disease (COVID-19). Moreover, the result finds that Baltic Dry Index is the most explosive and shows four bubbles, followed by Baltic Clean Tanker Index. The volatile behavior has been more frequent and pronounced since the second quarter of 2021, mainly instigated by the economic recovery. The results detect four bubbles in Baltic Dry Index caused by strong demand for raw materials and uncertainty restrictions. Furthermore, a single bubble in the Baltic Dirty Tanker Index is caused by the increasing oil price, growing demand for floating storage while burst due to new restrictions of the second wave, declining oil prices, and shortages of vessels. The need for oil products, logistical problems and the highest oil prices are the leading determinants of Baltic Clean Tanker index bubbles.
Keywords: Shipping industry; Shipping freight; Bubble; COVID-19; Generalized supremum ADF